Childbirth-Related Hospital Burden by Socioeconomic Status in a Universal Health Care Setting - Mah, Sarah Meghan; Sanmartin, Claudia; Harper, Sam; Ross, Nancy A (International Journal of Population Data Science, 2018)
Introduction Hospital utilization varies across socioeconomic and demographic strata in Canada, which has a universal health care system that grants essential services to everyone. Rates of adverse birth outcomes are known to differ among high and low SES women, but less is known of the excess burden attached to those outcomes across Canadian provinces. Objective To examine length of stay for childbirth relative to women’s socio-demographic characteristics, in the context of the Canadian universal health care system. Methods A population-based record linkage between the Canadian Community Health Survey (CCHS) cycles 3.1 (2005) and 4.1 (2007/8), and the Discharge Abstract Database (DAD) allowed the tracking of hospital utilization for linked survey respondents between 2005 and 2009. Hourly length of stay for delivery was modeled by socio-demographic factors, controlling for other clinical and individual-level characteristics. Results There were 7,166 complete delivery records from 5,570 female CCHS respondents who agreed to link and share their information. Women with the lowest income had on average, four-hour longer stays for vaginal delivery as compared to high-income women (IRR 1.07, 95% CI 1.02-1.13, p=0.01), and eight-hour longer stays for Caesarian delivery (IRR 1.08, 95% CI 0.95-1.22, p=0.23). A greater proportion of teenage pregnancy was seen for Aboriginal girls. Aboriginal status and rural area of residence were co-determinants of elevated length of stay. Conclusion The absence of egregious socio-demographic differences regarding childbirth is reassuring for the Canadian health care system. However, the persistence of marginally longer, and in turn, costlier visits for low-income and rural Aboriginal women is suggestive that policies of cash transfers during the prenatal period might be highly cost-effective if they achieve population-wide reductions in length of stay.